5x-(2(x-1)+2)=7x

Simple and best practice solution for 5x-(2(x-1)+2)=7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-(2(x-1)+2)=7x equation:


Simplifying
5x + -1(2(x + -1) + 2) = 7x

Reorder the terms:
5x + -1(2(-1 + x) + 2) = 7x
5x + -1((-1 * 2 + x * 2) + 2) = 7x
5x + -1((-2 + 2x) + 2) = 7x

Reorder the terms:
5x + -1(-2 + 2 + 2x) = 7x

Combine like terms: -2 + 2 = 0
5x + -1(0 + 2x) = 7x
5x + -1(2x) = 7x

Remove parenthesis around (2x)
5x + -1 * 2x = 7x

Multiply -1 * 2
5x + -2x = 7x

Combine like terms: 5x + -2x = 3x
3x = 7x

Solving
3x = 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
3x + -7x = 7x + -7x

Combine like terms: 3x + -7x = -4x
-4x = 7x + -7x

Combine like terms: 7x + -7x = 0
-4x = 0

Divide each side by '-4'.
x = 0

Simplifying
x = 0

See similar equations:

| 5s^2-26s+24=0 | | 1/4+1= | | 6y-9=2y+5 | | 73-u=200 | | -8-7=8x+22 | | 3+7m=11+3m | | 1x=19 | | 15a+2a=0 | | ln(x-8)+ln(x+7)=ln(x-57) | | y=1.62x+4.33 | | 6x(-8)+9(2x)=29 | | 2x=x^2 | | X^2-2x-35= | | -6x^2+12x=0 | | 6x+6x= | | 8x-2=5x+7 | | 5+x=3x-15 | | 5x+23=14x-58 | | y-2x=-4 | | -1.4x^2+1.2x+0.2=0 | | 4p=-240 | | 8(3x+2)=2(12x-5) | | 4=-240 | | 8+8= | | m^3-5m^2+3m+9=0 | | 10+3x=-2 | | 2*2+2= | | 4c^3-16c^2+12c=0 | | (x*13.8985-1387.07)+(x*707.096-13081.276)=0 | | 36x^2-9y^2= | | 15ab+2a=0 | | 2+3*5-8= |

Equations solver categories